Rural–urban differences in health among youth in northern Sweden: an outcome-wide epidemiological approach. Issue 1 (1st January 2019) - Jonsson, Frida; Goicolea, Isabel; San Sebastian, Miguel
ABSTRACT: The aim of this research was to contribute knowledge about rural–urban differences in health among young northern Swedish women and men. This study was based on the 2014 "Health on Equal Terms" survey, distributed in the four northernmost counties of Sweden, with complementary information on areas of residence classified as rural, semi-urban and urban from total population registers. The analytical sample included 2, 691 individuals who were selected using a probabilistic sampling method. Prevalence ratios were calculated in multivariable log-binomial regression analyses to measure the association between place of residence and nine outcomes covering three health dimensions (general, mental and lifestyle behaviours). The results indicated that daily smoking and being overweight were more common, while feelings of stress and psychological distress were less prevalent, among youths in rural as compared to urban areas. After including covariates, this pattern appeared stronger for young women, although the direction of the results also applied to young men, albeit without revealing significant differences. In conclusion, the findings from this study indicate that for youths – particularly young women – the rural setting may imply an increased risk of poor general health and lifestyle behaviours, while simultaneously playing a partially protective role for mental health.